Empowerment efforts to Moria in cervical cancer’s prevention - Elisabeth Surbakti; Julietta Hutabarat; Hanna Sriyanti Saragih (Jurnal Kesehatan Ibu dan Anak, 2020)
Empowerment of fertile age women who are married and become members of Batak Karo Protestant Church or it’s called Moria, with a participatory approach as an effort to build, explore and develop existing potentials by motivating and raising awareness of their potential so that a process of independence in cervical cancer prevention occurs. This study aims to empower Moria in the prevention of cervical cancer. The mixed research method. The qualitative was for empowerment efforts, while the quantitative method was for assessing the success of empowerment using a quasi-experimental design (pre-test-post-test group design without control). The qualitative analysis method uses interactive model analysis (data reduction, data presentation, and conclusion drawing/verification). The quantitative data were processed using univariate, bivariate analysis. The research was conducted in the working area of Padang Bulan Public health center in Medan Indonesia started from November 2016 to August 2017. The qualitative result was showed that there was still many Moria who did not know about cervical cancer prevention because they are ashamed, do not dare to come to health care, worried if the results are positive which can interfere with the next life process. Need the empowerment effort again to provide counseling on cervical cancer prevention. The quantitative result showed that there was an effect of Moria empowerment to knowledge (p-value=0.001) and attitude (p-value=0.001), and there was the effect of Moria empowerment on the action in cervical cancer prevention (p-value=0.001). The empowerment of Moria in cervical cancer prevention was very effective in increasing awareness, knowledge, attitudes, and actions of Moria in cervical cancer prevention.